2001
DOI: 10.1002/pse.87
|View full text |Cite
|
Sign up to set email alerts
|

Practical solutions to soil–structure interaction problems

Abstract: Interaction of a structure and its foundation with the soil is discussed in this paper, and some of the numerical and analytical methods that have been developed for the analysis of raft and piled raft foundations are presented. It is shown that the use of simple spring models for the soil behaviour can lead to erroneous result and it is recommended that their use should be discontinued. Simple finite layer techniques are also examined, and results are compared with those of three-dimensional finite element te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The characteristics of the superstructure can play a crucial role in the overall structure and foundation performance (Small 2001;Poulos 2016), and the main objective of this study is to investigate such effects in pile optimization considerations. In the current study, the superstructure stiffness is incorporated into the piled raft foundation analyses through the matrix condensation method.…”
Section: Condensed Superstructure Stiffness Matrixmentioning
confidence: 99%
“…The characteristics of the superstructure can play a crucial role in the overall structure and foundation performance (Small 2001;Poulos 2016), and the main objective of this study is to investigate such effects in pile optimization considerations. In the current study, the superstructure stiffness is incorporated into the piled raft foundation analyses through the matrix condensation method.…”
Section: Condensed Superstructure Stiffness Matrixmentioning
confidence: 99%
“…Gazetas and Mylonakis [9] and Mylonakis et al [10] emphasized importance of proper SSI analysis on response of bridges and provided important insight on failure of Hanshin Expressway bridge during Kobe earthquake. Small [11] developed SSI models showing how use of simple spring models for the soil behavior could lead to erroneous result and recommended that their use should be discontinued. In addition to that, they showed that the type of structure and its stiffness could have an effect on the deformation of the foundation.…”
Section: Introductionmentioning
confidence: 98%